Improvement in health status following cough-suppression physiotherapy for patients with chronic cough. - Patel, A; Watkin, G; Willig, B; Mutalithas, K; Bellas, H; Garrod, R; Pavord, I; Birring, S (2011)
Cough-suppression physiotherapy is a novel self-help therapy for chronic cough. We evaluated the effectiveness of cough physiotherapy in a pilot prospective observational study. We assessed cough-specific health-related quality of life (HRQOL) with the Leicester Cough Questionnaire (LCQ) and subjectively reported cough frequency and sleep disturbance in 23 patients with chronic cough refractory to medical therapy, before and after outpatient-based cough-suppression physiotherapy. Cough-suppression physiotherapy consisted of education, counselling, cough control, breathing retraining, and vocal hygiene. There was a significant improvement in cough-specific HRQOL after cough physiotherapy; mean (standard error of mean [SEM]) LCQ total score before 12.4 (0.9) versus after 15.1 (0.9); 95% confidence interval of difference -4.1 to -1.3; p < 0.001. The improvement in cough-specific HRQOL was greater than the LCQ minimal clinically important difference of 1.3. A significant improvement was seen in all LCQ domains: physical (p = 0.001), psychological (p < 0.001) and social (p < 0.04). There was a significant reduction in cough frequency scores (p = 0.002) and sleep disturbance scores (p = 0.02). Our findings suggest cough-suppression physiotherapy may lead to a clinically significant improvement in cough-specific HRQOL in patients with chronic cough.